2008
DOI: 10.1007/s00018-008-8575-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of muscle creatine kinase by phosphorylation in normal and diabetic hearts

Abstract: Protein kinase C (PKC) is an important signaling molecule in the heart, but its targets remain unclear. Using a PKC substrate antibody, we detected a 40-kDa phosphorylated cardiac protein that was subsequently identified by tandem mass spectroscopy as muscle creatine kinase (M-CK) with phosphorylation at serine 128. The forward reaction using ATP to generate phosphocreatine was reduced, while the reverse reaction using phosphocreatine to generate ATP was increased following dephosphorylation of immunoprecipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…All major PKC isoforms are also detected in mitochondria isolated by Percoll purification from normal hearts [31]. We and others have reported that levels of PKCb 2 and PKCe are increased in total cellular protein from diabetic hearts [11,12,19]. However, whether this is associated with changes in the levels of these isoforms in mitochondria from diabetic hearts is not known.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…All major PKC isoforms are also detected in mitochondria isolated by Percoll purification from normal hearts [31]. We and others have reported that levels of PKCb 2 and PKCe are increased in total cellular protein from diabetic hearts [11,12,19]. However, whether this is associated with changes in the levels of these isoforms in mitochondria from diabetic hearts is not known.…”
Section: Resultsmentioning
confidence: 96%
“…1A), an 80-kDa protein with increased phosphorylation and a 40-kDa protein with reduced phosphorylation, in hearts from diabetic rats. The 40-kDa protein was identified as M-CK, and further characterization was recently reported [19]. To identify the 80-kDa protein, the corresponding band was cut from the gel, subjected to in-gel digestion and the resulting peptides were analyzed by MS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Putative PKC Phosphorylation Site on sMiCK and CKM Is Required for the Regulation of NCX1 Activity-It has been shown that CKM is phosphorylated by PKC, possibly at Ser-128 (32). To examine the role of this serine residue in CK mediated recovery of the decreased NCX1 activity, plasmids encoding the Ser-128 equivalent mutants of sMiCK and CKM, namely sMiCK-S123A and CKM-S128A, were constructed and co-transfected with NCX1 into HEK293T cells.…”
Section: Regulation Of Namentioning
confidence: 99%